2005
DOI: 10.1159/000083906
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Viral Deoxyribonucleic Acid in Amniotic Fluid: Association with Fetal Malformation and Pregnancy Abnormalities

Abstract: Objective: To first test the hypothesis that the presence of viral nucleic acid in amniotic fluid (AF) is associated with an abnormal pregnancy outcome, and second, to determine if the overall rate of polymerase chain reaction (PCR) positivity and the distribution of virus types vary geographically. Study Design: Cytomegalovirus (CMV), parvovirus B19, adenovirus, enterovirus, herpes simplex virus, Epstein-Barr virus, and respiratory syncytial virus nucleic acids were sought in 423 AF samples obtained for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
4
33
3
3
Order By: Relevance
“…Of 1187 unique amniocentesis samples analysed in four separate studies of sonographically normal pregnancies, more than 1 in 20 (5.4%) contained adenoviral DNA ( Van den Veyver et al, 1998;Wenstrom et al, 1998;Baschat et al, 2003;Reddy et al, 2005). Remarkably, subsequent studies have detected no increased morbidity in infants following prenatal infection with adenovirus, as determined by PCR of amniocentesis samples (Miller et al, 2009), suggesting that prenatal infection, similar to postnatal infection, with species C adenoviruses is largely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Of 1187 unique amniocentesis samples analysed in four separate studies of sonographically normal pregnancies, more than 1 in 20 (5.4%) contained adenoviral DNA ( Van den Veyver et al, 1998;Wenstrom et al, 1998;Baschat et al, 2003;Reddy et al, 2005). Remarkably, subsequent studies have detected no increased morbidity in infants following prenatal infection with adenovirus, as determined by PCR of amniocentesis samples (Miller et al, 2009), suggesting that prenatal infection, similar to postnatal infection, with species C adenoviruses is largely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a likely fetal pathogen (Towbin et al, 1994;Van den Veyver et al, 1998;Oyer et al, 2000;Baschat et al, 2003;Reddy et al, 2005), adenovirus DNA is also detected in the amniotic fluid from apparently normal pregnancies. Of 1187 unique samples in four large studies, 64 (5.4%) contained adenoviral DNA ( Van den Veyver et al, 1998;Wenstrom et al, 1998;Baschat et al, 2003;Reddy et al, 2005), which compares favourably with 6% adenovirus DNA-positive samples among the normal controls in the present study (Table 1). And, as is the case with children infected post-natally, adenoviral DNA is retained in latently infected T lymphocytes for years following primary infection (Garnett et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified that the sexually transmitted pathogens Chlamydia trachomatis and Neisseria gonorrhoeae, along with the uropathogen E. coli and yeast Candida spp., are also infrequently associated with chorioamnionitis (122,(125)(126)(127)(128). Viral etiologies of chorioamnionitis include adenovirus, cytomegalovirus, enterovirus, and, less frequently, respiratory syncytial virus and Epstein-Barr virus (129)(130)(131)(132). Of the microorganisms associated with chorioamnionitis, the human Ureaplasma spp.…”
Section: Causative Agents Of Chorioamnionitismentioning
confidence: 99%